Host-pathogen biotic interactions shaped vitamin K metabolism in Archaeplastida. Issue 1 (December 2018) - Cenci, U.; Qiu, H.; Pillonel, T.; Cardol, P.; Remacle, C.; Colleoni, C.; Kadouche, D.; Chabi, M.; Greub, G.; Bhattacharya, D.; Ball, S.
Abstract Menaquinone (vitamin K2 ) shuttles electrons between membrane-bound respiratory complexes under microaerophilic conditions. In photosynthetic eukaryotes and cyanobacteria, phylloquinone (vitamin K1 ) participates in photosystem I function. Here we elucidate the evolutionary history of vitamin K metabolism in algae and plants. We show that Chlamydiales intracellular pathogens made major genetic contributions to the synthesis of the naphthoyl ring core and the isoprenoid side-chain of these quinones. Production of the core in extremophilic red algae is under control of a menaquinone (Men) gene cluster consisting of 7 genes that putatively originated via lateral gene transfer (LGT) from a chlamydial donor to the plastid genome. In other green and red algae, functionally related nuclear genes also originated via LGT from a non-cyanobacterial, albeit unidentified source. In addition, we show that 3–4 of the 9 required steps for synthesis of the isoprenoid side chains are under control of genes of chlamydial origin. These results are discussed in the light of the hypoxic response experienced by the cyanobacterial endosymbiont when it gained access to the eukaryotic cytosol.